2013
DOI: 10.1590/s0102-311x2013000900009
|View full text |Cite
|
Sign up to set email alerts
|

Incapacidades físicas em pessoas acometidas pela hanseníase no período pós-alta da poliquimioterapia em um município no Norte do Brasil

Abstract: Chronic sequelae and disabilities are one of the main problems in leprosy. The current study aimed to estimate the prevalence of disabilities in leprosy patients after successfully completing multidrug therapy in Araguaína, Tocantins State, Brazil. This was a cross-sectional study including 282 cases diagnosed from 2004 to 2009. The degrees of disability at diagnosis and at discharge from treatment were collected from medical records and the National Information System for Notifiable Diseases (SINAN). A simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The group aged between 30 and 59 years old includes the Brazilian economically active population, interval that the disease hinders labor activities, forcing individuals to stop working or retire early, decreasing the quality of life of workers [28,36,37]. In this sense, health services should focus on preventive measures by actively seeking individuals in this age group, in addition to diagnosis of cases, providing timely treatment, and early identification of lesions, the purpose of which is also to prevent physical disability.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The group aged between 30 and 59 years old includes the Brazilian economically active population, interval that the disease hinders labor activities, forcing individuals to stop working or retire early, decreasing the quality of life of workers [28,36,37]. In this sense, health services should focus on preventive measures by actively seeking individuals in this age group, in addition to diagnosis of cases, providing timely treatment, and early identification of lesions, the purpose of which is also to prevent physical disability.…”
Section: Plos Onementioning
confidence: 99%
“…In this sense, health services should focus on preventive measures by actively seeking individuals in this age group, in addition to diagnosis of cases, providing timely treatment, and early identification of lesions, the purpose of which is also to prevent physical disability. Early interventions prevent or minimize the high social costs leprosy imposes from removing this population from productive activities and social relationships [28,[36][37][38].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A study of patients residents in the state of Maranhão showed a progressive increase in the chances of developing physical disability among those older than 15 years, ranging from 3 to 10.4 times more [18]. Considering the duration of the disease is directly related to age and, given the chronic pro le of leprosy effects, increasing age may result in more advanced disabilities [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the quality of life of patients with functional limitations is adversely affected in both physical health and environmental domains. In addition, sequelae caused by leprosy, such as disability and nerve damage, are major risk factors for Parkinson's disease [26][27][28][29]. Therefore, in the future, the city should improve the early detection of leprosy, strengthen prevention and treatment efforts, reduce the incidence of disability in patients, and eliminate the harm of leprosy [30].…”
Section: ) Diagnosis and Disabilitymentioning
confidence: 99%